Identification and Estimation of Intra-Firm and Industry Competition via Ownership Change - Michel Christian (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
This paper proposes and empirically implements a framework for analyzing industry competition and the degree of joint profit maximization of merging firms in differentiated product industries. Using pre- and post-merger industry data, I am able to separate merging firms' intra-organizational pricing considerations from industry pricing considerations. The insights of the paper shed light on a long-standing debate in the theoretical literature about the consequences of organizational integration. Moreover, I propose a novel approach to directly estimate industry conduct that relies on ownership changes and input price variation. I apply my framework using data from the ready-to-eat cereal industry, covering the 1993 Post-Nabisco merger. My results show an increasing degree of joint profit maximization of the merged entities over the first two years after the merger, eventually leading to almost full maximization of joint profits. I find that between 14.3 and 25.6 percent of industry markups can be attributed to cooperative industry behavior, while the remaining markup is due to product differentiation of multi-product firms.
urn:nbn:de:bvb:19-epub-17233-4
Keywords: 330; Identification of Market Structure; Post-merger Internalization of Profits; Conduct Estimation; Ex-post Merger Evaluation; Estimation of Synergies